Effect of tin loading on physical properties and phase transformation of as-synthesized Zn-Sn-O compound powder synthesized by co-precipitation method - Kahattha, C.; Chongsri, K.; Noonuruk, R.; Mekprasart, W.; Pecharapa, W. (My University, 2014)
Zinc-Tin oxide compounds (Zn-Sn-O) were successfully prepared via a facile co-precipitation process using zinc dichloride dihydrate as the zinc source and tin tetrachloride pentahydrate as an additive source. The as-prepared product of Zn-Sn-O powders with various Sn additive contents (0-60 %wt) were obtained without calcinations process. The effect of Sn additive on structural and microstructure properties of the samples were characterized by X-ray diffraction(XRD), scanning electron microscope(SEM). The results indicate that the crystallinity and morphologies of ZnO nanoparticles are significantly influenced by Sn additive. The phase formations of Zn-Sn-O including ZnO, ZnSn(OH)6 were observed depending on the Sn-additive composition.
Keywords: Co-precipitation; Tin; Zinc oxide